The Influence of Career Development and Work Environment on Employee Performance Through Job Satisfaction at Bank Negara Indonesia Muara Bungo Branch - Sari, Wulan; Zahari MS; Sudirman Sudirman (International Journal of Advanced Multidisciplinary, 2023)
This research aims to determine and analyze the influence of career development and work environment on employee performance through job satisfaction for employees at Bank BNI Muara Bungo Branch. The method used in this research is descriptive verification and quantitative methods. In this research, the sampling technique used was a nonprobability sampling approach with a purposive sampling method. Based on the approach, it can be seen that the number of samples is 77 people. This research uses the PLS analysis method. Based on the description of career development, work environment, job satisfaction and employee performance at Bank BNI Muara Bungo Branch, it shows that career development is in the good category. Then the Work Environment shows the good category. Next, Job Satisfaction is in the satisfied category. Meanwhile, employee performance is in the high category. Based on the research results, Career Development has a positive and significant effect on Job Satisfaction, Work Environment has a positive and significant effect on Job Satisfaction, Career Development has a positive and significant effect on Employee performance, Work Environment has no significant effect on Employee performance, Job Satisfaction has a positive and significant effect on Employee performance, Career Development have a positive and significant effect on Employee performance through Job Satisfaction, Work Environment has a positive and significant effect on Employee performance through Job Satisfaction at Bank BNI Muara Bungo Branch.